Pengembangan Aplikasi Pembelajaran Grammar Bahasa Inggris Menggunakan Gamifikasi dan ChatGPT - Lintang Pramudya Anpurnan; Andreas Nugroho Sihananto; Pratama Wirya Atmaja (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Education serves as the main pillar in the effort to develop human resources, continually evolving in line with the progress of time. Within the realm of education, English language learning plays a crucial role. However, the process of English language learning often faces challenges, including low levels of student motivation. This research explores the use of gamification with integrated chatGPT as an innovative solution capable of boosting student motivation and making learning more engaging and effective. Adapting previously proposed methodologies, this application is web-based, developed using Laravel, and tested using Likert scale. The testing yielded a satisfactory average result of 83%, with a 15.64% increase in user scores. The findings of this research provide a positive contribution to enhancing the quality of English language education in Indonesia, particularly at the Junior High School level.